Desenhando a ideia de uma “avenida feliz”: imagens das histórias e memórias da Avenida Senhor dos Passos - Oliveira, Sidiney de Araujo (2010)
This work aims to discuss the images, literal or textual, which are related with the perception of the Senhor dos Passos Avenue in Feira de Santana, Bahia, as a essential factor for the urban visual memory production between 1977 and 2003, in a dialogical approach and nonlinear. Throughout the city’s history, this important avenue of the urban center has been changed from a residential area, address of the economic and political elite, to a public area of highly characteristic trade. This transition produced ineffaceable signs that have been reverberated on the reinvention of the city places. In this process, the design has suggested a practical review in the urbanistics and architectural questions of the houses to get back the image and the imaginary appropriation of the desired city. The descendent of the elites, who have lived there for years, have been regretted this changing and they are seeking to form a visual memory for that avenue which was in their urban experiences, “a happy avenue”. The analysis will be established in literary works, interviews to residents and ex-residents of the Senhor dos Passos Avenue, newspapers and photos of various historical moments, taking as a theoretical and methodological system of reference, authors who research the collective memory, like Marice Halbwachs, about the places of memory like Pierre Nora and Michel Pollak and besides João do Rio, with the Alma encantadora das ruas. It is possible to observe in the sources of investigation some guidelines that expect to consolidate a memory which can ennoble the past of the Senhor dos Passos Avenue.